Identifying sustainability communicators in urban regeneration: Integrating individual and relational attributes. (1st February 2018) - Alexandrescu, Filip M.; Pizzol, Lisa; Zabeo, Alex; Rizzo, Erika; Giubilato, Elisa; Critto, Andrea
Abstract: The paper advances a conceptualization of sustainability in urban regeneration as communicative practice taking place within networks of social actors. To demonstrate the potential of this perspective, we propose an interdisciplinary methodology integrating social network analysis from sociology and multi-criteria decision analysis (fuzzy logic) from operations research to calculate a sustainability communicator score for each actor involved in a regeneration network. The score is based on three dimensions: a sustainability vision (relying on the three pillar model of sustainability), a formal network influence dimension (based on organizational practice and decision-making position) and an informal network influence dimension (drawing on degree, betweenness, eigenvector and closeness centrality measures from social network analysis). The framework allows the identification and ranking of sustainability communicators, based on the preferences of specific users, while also allowing for variable degrees of vagueness. We illustrate the methodology by means of a case study of a social network of actors (N = 28) involved in the sustainable regeneration of a brownfield site in Porto Marghera, Venice, Italy. The methodology is expandable beyond the actor level to allow for the ranking of more complex network configurations for promoting sustainability. Highlights: Sustainability in urban regeneration is conceptualized as communicative practice. A methodological framework for identifying sustainability communicators is developed. The framework integrates actors' sustainability vision and their social network position to identify the top communicators. The resulting network map allows sustainability promoters to use such communicators to spread their views amid stakeholders.